Handbook on advancements in smart antenna technologies for wireless networks [ - Cheng, Jun , 1964-; Ohira, Takashi , 1955-; Sun, Chen , 1977-
"This book is a comprehensive reference source on smart antenna technologies featuring contributions with in-depth descriptions of terminologies, concepts, methods, and applications related to smart antennas in various wireless systems"--Provided by publisher